Casos escogidos de Derecho antitrust europeo - Alfonso Luis Calvo Caravaca (Estudios de Deusto, 2012)
This section analyses a number of selected cases on European antitrust law, including Judgements and Decisions on European Antitrust Law, abuse of a dominant position, unlawful arrangements (cartels) and mergers. The cases commented on this section maintain their consecutive numeration initiated on the vol. 54/1 (January-June 2006).